Choosing an Appropriate Live Feed for Larviculture of Marine Fish - Cortney L. Ohs; Eric J. Cassiano; Adelaide Rhodes (EDIS)
FA167, a 7-page illustrated fact sheet by Cortney L. Ohs, Eric J. Cassiano, and Adelaide Rhodes, discusses the pros and cons of using rotifers, brine shrimp, and copepods as live food for marine fish larvae. Includes references. Published by the UF Program in Fisheries and Aquatic Sciences, December 2009.